2004
DOI: 10.1111/j.0001-6349.2004.00401.x
|View full text |Cite
|
Sign up to set email alerts
|

Menstrual bleeding patterns in pre‐ and perimenopausal women: a population‐based prospective diary study

Abstract: Irregularity of cycle lengths at the end of the fertile period is common, and is accompanied by an increased inter- and intraindividual variation in the length and heaviness of bleeding episodes, including increased frequency of prolonged bleeding and spotting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 11 publications
1
6
0
Order By: Relevance
“…A similar result was seen in a Danish study which observed obese women were more likely to report menstrual flooding but not prolonged menstrual bleeding 18 . In the SWAN Daily Hormone Study, obesity was also associated with 3 or more days of heavy bleeding 31 .…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…A similar result was seen in a Danish study which observed obese women were more likely to report menstrual flooding but not prolonged menstrual bleeding 18 . In the SWAN Daily Hormone Study, obesity was also associated with 3 or more days of heavy bleeding 31 .…”
Section: Discussionsupporting
confidence: 84%
“…A similar result was seen in a Danish study, which observed that obese women were more likely to report menstrual flooding but not prolonged menstrual bleeding. 18 In the SWAN Daily Hormone Study, obesity was also associated with three or more days of heavy bleeding. 31 The Michigan Bone Health and Metabolism Study did not find an association between menses duration and BMI in women aged 25-50 years.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…73 In a Danish study of premenopausal and perimenopausal women, obesity was associated with higher frequency of flooding. 56 In the SWAN DHS, heavier women had shorter cycles than women with BMI <25kg/m 2 ; 43 but obesity was also associated with an increased number of heavy bleeding days. 17 The Harvard Study of Moods and Cycles found the age-adjusted incidence rate of perimenopause to be 1.58 times higher among obese women as compared to normal weight women.…”
Section: Factors That Influence Menstrual Characteristics During the mentioning
confidence: 96%
“…In a population-based menstrual calendar study of Danish women, onset of irregular cycles as women entered the menopausal transition was associated with increased variability in the duration of bleeding, with increased frequency of spotting and bleeds lasting 10 or more days and with increased variability in women’s subjective reports of the amount of menstrual flow. 56 …”
Section: Characteristics Of Menstrual Bleedingmentioning
confidence: 99%